2020
DOI: 10.1088/1757-899x/734/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Research results of planetary roller screw transmission for high-precision mechanisms

Abstract: In the article experimental survey results of planetary roller screw drive for usage in high precision parallel structure mechanisms for space application are considered. The drive was developed in Academician M.F. Reshetnev Information Satellite System. Roller screw is perspective type of precision linear drives which excels in several characteristics extensively used in modern time ball screws. Ground tests conducting methodology, tests scheme of the developed roller screw are described. Key parameters of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The GDU (Figure 3) is developed as a modular transformer of a rotary input movement to a secured specified linear motion. Studies on space-qualified screw mechanisms can be found in [16][17][18]. A modified ball screw from August Steinmeyer GmbH was chosen for the GDU.…”
Section: Gripper Drive Unitmentioning
confidence: 99%
“…The GDU (Figure 3) is developed as a modular transformer of a rotary input movement to a secured specified linear motion. Studies on space-qualified screw mechanisms can be found in [16][17][18]. A modified ball screw from August Steinmeyer GmbH was chosen for the GDU.…”
Section: Gripper Drive Unitmentioning
confidence: 99%
“…Based on new theory and mechanism, Morozov and Zhdanov 43 explored new types of the PRSM considering geometric parameters, thread helix angles, and roller diameter ratios. Boyko et al 44 designed a high-precision mechanism with split nut for aerospace communication equipment. The important parameters such as transmission accuracy, axial stiffness and working lifetime of the PRSM were obtained through experiments.…”
Section: Errors Analysismentioning
confidence: 99%
“…(Jones, 2013). Owning to its superior characteristics, PRSM has been widely used in aerospace (Blinov et al, 2019), satellites (Boyko et al, 2020), radio telescopes (Mamaev et al, 2015), oil exploration (Parker et al, 2018), medical equipment (Rosenberg et al, 1982) and many other fields. With the rapid development of mechatronics, particularly the electro-mechanical actuator (EMA), the application of PRSM will be further expanded.…”
Section: Introductionmentioning
confidence: 99%